THE EFFECT OF ORGANIZATIONAL JUSTICE AND CONFLICT MANAGEMENT ON LOYALTY OF VOCATIONAL HIGH SCHOOL TEACHERS IN CENTRAL JAKARTA INDONESIA - Ria Aprilia Fredy; Masduki Ahmad; Heru Santoso (Teunuleh Publisher, 2020)
The purpose of this study is to comprehensively describe and describe the effect of organizational justice and conflict management on loyalty of vocational school teachers in central Jakarta indonesia. This research was conducted to Private Vocational High Schools (SMK) in central Jakarta. Research methods This study uses a quantitative research survey method, as for analyzing data using path analysis. Path analysis technique in this study is to determine the causal relationship between variables or the direct influence of exogenous variables on endogenous variables. Endogenous variables in this study are teachers loyalty, while the exogenous variables in this study are organizational justice and conflict management. Data collection was carried out through questionnaire filling. Based on the calculation results obtained by path analysis 1) the direct effect of organizational justice on teachers loyalty, the value of the path coefficient of 0.425 and tcount of 6.6964, meaning that organizational justice has a direct positive effect on teachers loyalty can be accepted increasing organizational justice resulting in increased teachers loyalty. 2) the direct effect of conflict management on the teachers loyalty, path coefficient of 0.225 and tcount of 3.378. Means, the direct influence of conflict management on teachers loyalty, the value of the path coefficient of 0.425 and tcount of 6.6964. 3)organizational justice has a direct positive effect on teachers loyalty can be accepted. That is, increasing organizational justice results in increased teachers loyalty.